Implementation of Watson's Theory in a Patient with Breast Cancer: A Case Study - Adib-Hajbaghery, Mohsen; Bolandianbafghi, Shahnaz; Nabizadehgharghozar, Zohreh (Advances in Nursing & Midwifery, 2020)
Introduction: Patients who are suffering from breast cancer have numerous problems. Watson's Theory of Human Caring seems to be proper in caring for these patients. This theory stresses the humanistic aspects of nursing as they interfere with scientific knowledge and nursing practice. This study implemented Watson's theory in preparing a Persian woman with breast cancer to accept the treatment process. Methods: In this case study, the patient was selected from the patients referring to a hospital in a city in Iran. Open-ended interview and observation were used to collect the required data. The process of the study was done in five stages. Results: After implementation of Watson's theory in a five-step interview, the patient's disappointment and despair were reduced and the patient agreed to continue the treatment process. Conclusions: Watson's theory of caring is likely to bring love and hope back to patients with breast cancer in bad physical and mental conditions. By applying 10 caring factors of this theory, a humanitarian relationship is established with the patient; this relationship is based upon love and hope. The patient is able to express her feelings and continue the treatment process by trusting God, applying her spirituality, and gaining supports from family and friends.